KEMAMPUAN KOMUNIKASI MATEMATIS SISWA DALAM MATERI PROGRAM LINEAR DITINJAU DARI GAYA BELAJAR VISUAL - Benazira Bharti; Hamdani Hamdani; Asep Nursangaji (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThe purpose of this study was to study students' mathematical communication skills in a linear program in terms of visual learning styles at MAN 1 Pontianak. The method used is descriptive method in the form of survey research. The data source used in this study was the students of class XI MIPA 1 at MAN 1 Pontianak. Data collection tools used were non-test consisting of a questionnaire to measure visual learning styles and written tests to understand students' communication skills. Based on the test results, students are able to connect real objects into mathematical ideas, students are able to describe everyday events using language or mathematical symbols and are able to explain some mathematical problems into the form of images. The results of data analysis show that the communication skills of students with visual learning styles are of good qualityKeywords: Linear Program, Mathematical Communication, Visual Learning Style